SCIENTIFIC AND THEORETICAL APPROACHES TO THE TYPES OF DYSTOPIAN NOVELS IN THE WORLD LITERATURE (Scientific journal of the Fergana State University, 2023)
The article is devoted to the emergence, classification and development of the term "dystopia", which is considered a new genre in literary criticism and has caused considerable controversy among literary scholars and critics. The use of the terms dystopia and anti-utopia in science, as well as their differences are considered in detail. The article reflects the scientific and theoretical views of world writers on dystopia and anti-utopian work. The author of the article expressed a scientific-theoretical attitude about the development of dystopia and its place in contemporary literary studies.